PENGARUH PRICE EARNINGS RATIO, DIVIDEND YIELD DAN MARKET TO BOOK RATIO TERHADAP STOCK RETURN DI BURSA EFEK INDONESIA - FARAH MARGARETHA; IRMA DAMAYANTI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2008)
The purpose of this research is to analyze the effect of stock return. This research used for 108 non financial firms which listed in Indonesian Stock Exchange during 2004-2007. Independent variables of this research are price earnings ratio, dividend yield and market to book ratio. Dependent variable is stock return. The analysis methods was used are multiple regression analysis. The result from this research shows that price earnings ratio, dividend yield, and market to book ratio have a relationship effect to stock return. So in determining stock return, investors has to consider of price earnings ratio, dividend yield and market to book ratio variables.